What does integrated ecosystem assessment mean to policy-makers and scientists working in the Atlantic? Implications for ocean science diplomacy - Polejack, Andrei; Ramírez-Monsalve, Paulina; Wisz, Mary S. (Frontiers in Marine Science, 2023)
An important goal of Integrated Ecosystem Assessment (IEA) is to be an inclusive, evidence-based process to engage stakeholders, in support of ecosystem-based management. IEA is resource intensive, requiring the engagement of personnel, experts from many disciplines, public and private institutions, and including issues of technology, infrastructure, capacity building, etc. Stakeholders such as policy-makers and scientists in influential decision-making roles often determine the level of investment when committing to an IEA. It is thus critical to understand how these specific stakeholders understand and perceive IEA, as well as their motivations for engagement. We interviewed government officials, science managers and scientists whose decisions are critical for mobilizing resources (time, expertise and funding) in support of ecosystem based management (and potentially IEA) in the Atlantic Ocean. The interviews aimed at documenting their perceptions of IEA, and their motivations to engage in the process. Our results show that most of these research and policy stakeholders are generally unaware of, or have misconceptions about IEA concepts. Those who expressed awareness of IEA considered IEA as unfit to address most policy and managerial goals. We propose that the IEA process could be improved by promoting inclusivity and applying ocean science diplomacy. We see that these two aspects (inclusivity and science diplomacy) can help research and policy stakeholders understand the true meaning of IEA through negotiating, and by strengthening and diversifying the involvement of international stakeholders. We advocate that the scoping phase of an IEA is of critical importance and should be core to the whole process. It is during the scoping phase that stakeholders are identified and engaged. With their involvement, there is a need to make their interests visible and respected. During the scoping phase, a safe and open space needs to be secured, so these interests can be negotiated and mutual understanding on concepts, roles in the process and the possible outcomes are achieved. This article is part of the Mission Atlantic Project (Horizon 2020) which is designed to conduct IEAs in the Atlantic Ocean.